Seismic Response Analysis In The Singaran Pati Sub-District Area of Bengkulu City Using Equivalent Linear And Non-Linear Approaches - Priani, Anggela Agus; Misliniyati, Rena; Amri, Khairul; Mase, Lindung Zalbuin; ‎Hardiansyah, Hardiansyah (Universitas Tribhuwana Tunggadewi Malang, 2024)
Bengkulu City is prone to earthquakes due to its proximity to the meeting point of two active tectonic plates. Singaran Pati sub-district has six villages that are the center of the sub-district government, trade in goods and services, defense, and health centers. This study aims to determine the ground response in the Singaran Pati sub-district due to earthquake wave propagation. The one-dimensional seismic wave propagation modeling method is linear equivalent and non-linear, similar to the Pressure Dependent Hyperbolic (PDH) model, which propagates earthquake waves from the bedrock to the surface. This research resulted in maximum earthquake acceleration or Peak Ground Acceleration (PGA) parameters, acceleration spectra response, earthquake wave acceleration, and amplification factor. The PGA value and the amplification factor of the equivalent linear and non-linear models are the largest in the eastern ring sub-district, 0.53 g and 0.45 g. The results of the acceleration spectra response analysis of equivalent linear and non-linear passed the SNI 1726: 2019 design with the most significant value in the equivalent linear model of 2.38 g while the non-linear was 2.01 g. The most considerable earthquake wave acceleration value in the equivalent linear model is 0.53 g, and the smallest value in the non-linear is 0.31 g. The results of this study show that the equivalent linear model produces higher values than the non-linear model. The equivalent linear model shows an overestimation that causes the maximum acceleration value to be greater than the non-linear model, so the non-linear model is more appropriate to use because it is more by the conditions in the field.